Respuesta :
Answer:
[tex]x=4/55\\y=-69/55[/tex]
Step-by-step explanation:
[tex]4x+9y-9y=-11-9y\\4x=-9y-11\\[/tex]
[tex]x=\frac{-9y-11}{4}\\-3(\frac{-9y-11}{4})+7y=-9[/tex]
[tex]\frac{55}{4} y=\frac{-69}{4}[/tex]
[tex]y=\frac{-69}{55}[/tex]
[tex]x=\frac{-9(-69/55)-11}{4}\\x=\frac{4}{55}[/tex]
Answer:
(- 4, - 3 )
Step-by-step explanation:
Given the 2 equations
- 4x + 9y = - 11 → (1)
- 3x + 7y = - 9 → (2)
Multiplying (1) by 3 and (2) by - 4 and adding will eliminate the term in x
- 12x + 27y = - 33 → (3)
12x - 28y = 36 → (4)
Add (3) and (4) term by term to eliminate x
- y = 3 ( multiply both sides by - 1 )
y = - 3
Substitute y = - 3 into either of the 2 equations and evaluate for x
Substituting into (1)
- 4x + 9(- 3) = - 11
- 4x - 27 = - 11 ( add 27 to both sides )
- 4x = 16 ( divide both sides by - 4 )
x = - 4
Solution is (- 4, - 3 )